Non-invasive in vivo study of the Trypanosoma vivax infectious process consolidates the brain commitment in late infections. - Simon D'Archivio; Alain Cosson; Mathieu Medina; Thierry Lang; Paola Minoprio; Sophie Goyard (Public Library of Science (PLoS), 2013)
Trypanosoma vivax, one of the leading parasites responsible for Animal African Trypanosomosis (Nagana), is generally cyclically transmitted by Glossina spp. but in areas devoid of the tsetse flies in Africa or in Latin American countries is mechanically transmitted across vertebrate hosts by other haematophagous insects, including tabanids. We followed on from our recent studies on the maintenance of this parasite in vivo and in vitro, and its genetic manipulation, by constructing a West African IL1392 T. vivax strain that stably expresses firefly luciferase and is fully virulent for immunocompetent mice. We report here on a study where murine infection with this strain was monitored in vivo using a non-invasive method. Study findings fully support the use of this strain in the assessment of parasite dynamics in vivo since a strong correlation was found between whole body light emission measured over the course of the infection and parasitemia determined microscopically. In addition, parasitemia and survival rates were very similar for mice infected by the intraperitoneal and sub-cutaneous routes, except for a longer prepatent period following sub-cutaneous inoculation with the parasite. Our results clearly show that when administered by the subcutaneous route, the parasite is retained few days in the skin close to the inoculation site where it multiplies before passing into the bloodstream. Ex vivo bioluminescence analyses of organs isolated from infected mice corroborated our previous histopathological observations with parasite infiltration into spleen, liver and lungs. Finally, our study reinforces previous observations on the presence of the parasite in the central nervous system and consequently the brain commitment in the very late phases of the experimental infection.